ШИМОЛИ-ҒАРБИЙ ҚИЗИЛҚУМНИНГ НОЁБ ВА ЙЎҚОЛИШ ХАВФИ ОСТИДАГИ ҲАЙВОН ТУРЛАРИ ҲАМДА УЛАРНИ МУҲОФАЗА ҚИЛИШ ЧОРАЛАРИ - Турекеева, Альфия Жиенбековна; Шарибаева, Умида Уразбай қизи (SCIENCE and SOCIETY, 2026)
The article provides a detailed analysis of rare and endangered reptile species found in the North-Western Kyzylkum region. During the study, the herpetofauna of the territory, the main anthropogenic factors, population dynamics, and the effectiveness of conservation measures were studied. The results showed that the decline in the number of some species is associated with habitat reduction, illegal hunting, the transport factor, and increased economic activity. Practical recommendations have been developed for the conservation of reptiles and ensuring population stability in the region.